Pengaruh Penggunaan Pasir Menggala Kabupaten Rokan Hilir Pada Campuran Laston Lapis Aus - Eka Candra Safrizal; Sri Djuniati; Yosi Alwinda (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Menggala sand is one of the natural sand obtained from the mound excavation located in the Province of Riau, and if the terms of the costs of using natural sand is certainly cheaper than the fine aggregates quarry result, it is not required additional costs for the fragmentation. Use of Menggala sand still limited and not optimal so that there should be research on the use Menggala sand as fine aggregate against asphalt concrete wearing course (AC-WC) with reference to the Specifications of Bina Marga 2010 3rd Revision. The purpose of this study was to determine the characteristics (properties) of natural Menggala sand whether it meets the requirements to be used as a mixture of AC-WC and influence the use of Menggala sand on performance or quality AC-WC through an examination of the characteristics of Marshall. Specifications of Bina Marga 2010 3rd Revision restricting the use of natural sand 15% of the total weight of the mixture of aggregate. Given the low cost of natural sand use in this study tested levels of sand with a variation of 0%, 5%, 10%, 15% and 20%. The results showed that a mixture of AC-WC with Menggala sand as fine aggregate eligible VMA (voids in mineral aggregate), VIM (voids in the mix), VFA (voids filled with asphalt), stability, Flow and Index of Retained Strength (IRS ) determined by the Specifications of Bina Marga 2010 3rd Revision to 20% sand content with optimum bitumen respectively - were based on variations in the sand content of 6.3%, 6.33%, 6.15%, 6.1% and 5.925%.Keywords: Menggala sand, Asphalt Concrete Wearing Course (AC-WC), Spesification of Bina Marga 2010, and Marshall characteristic